No convincing association between post‐operative delirium and post‐operative cognitive dysfunction: a secondary analysis. Issue 10 (31st August 2016) - Franck, M.; Nerlich, K.; Neuner, B.; Schlattmann, P.; Brockhaus, W. R.; Spies, C. D.; Radtke, F. M.
Abstract : Background: Post‐operative delirium and post‐operative cognitive dysfunction (POCD) are both common but it has not been clarified how closely they are associated. We aimed to assess the possible relationship in a secondary analysis of data from the 'Surgery Depth of anaesthesia and Cognitive outcome'‐ study. Methods: We included patients aged ≥ 60 years undergoing non‐cardiac surgery planned for longer than 60 min. Delirium was assessed according to the Diagnostic and Statistical Manual of Mental Disorders IV criteria in the post‐anaesthesia care unit (PACU) as well as within the first week after surgery. Cognitive function was assessed with a neuropsychological test battery. Multivariable analysis of POCD was performed with consideration of predisposing and precipitating factors. Results: Of 1277 randomized patients, 850 (66.6%) had complete data. Delirium was found in 270 patients (32.9% of 850). We detected POCD in 162 (20.9% of 776) at 1 week and in 52 (9.4% of 553) at 3 months. In multivariable analysis ( n = 808), delirium had no overall effect on POCD ( P = 0.30). Patients with no delirium in PACU but with postoperative delirium within 7 days had an increased risk of POCD at 3 months (OR = 2.56 (95%‐confidence interval: 1.07–6.16), P = 0.035). No significant association was found for the other subgroups. Conclusions: There is no clear evidence that postoperative delirium is independently associated with POCD up to 3 months.